Loss of Mammographic Tissue Homeostasis in Invasive Lobular and Ductal Breast Carcinomas vs. Benign Lesions - Gerasimova-Chechkina, Evgeniya; Toner, Brian C.; Batchelder, Kendra A.; White, Basel; Freynd, Genrietta; Antipev, Igor; Arneodo, Alain; Khalil, Andre (Frontiers in Physiology, 2021)
The 2D wavelet transform modulus maxima (WTMM) method is used to perform a comparison of the spatial fluctuations of mammographic breast tissue from patients with invasive lobular carcinoma, those with invasive ductal carcinoma, and those with benign lesions. We follow a procedure developed and validated in a previous study, in which a sliding window protocol is used to analyze thousands of small subregions in a given mammogram. These subregions are categorized according to their Hurst exponent values (H): fatty tissue (H≤0.45), dense tissue (H≥0.55), and disrupted tissue potentially linked with tumor-associated loss of homeostasis (0.45